Estimación del índice de mérito total del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia 11 de Noviembre - Fernández Carrillo, Andye Alejandra (2023)
The objective of this project is to estimate the total merit index of the sustainable genetic improvement program for dairy cattle in the 11 de Noviembre parish in the Latacunga canton, using benefit functions, with the purpose of carrying out a genetic improvement program sustainable production of dairy cattle, to achieve greater profits in dairy production, which leads to a better quality of life for producers with greater economic returns. To know the real situation, a descriptive research was used, of an observational nature, with the support of techniques and instruments for collecting information, evidencing the economic activities, the bovine tape measure for the weight of the bovines, the lactodensimeter to measure the temperature and milk density and the BLUP (Best linear unbiased predictor) evaluation system that helped predict the genetic value of cattle; 43 cattle from 11 producers were taken into account; The results showed animals with maximum ranges in the response to selection, showing the maximum value in daily weight gain of 260.3 (gr/day) corresponding to a one-year-old male bovine, it is estimated that in the fourth generation of this bovine will obtain 801.2 (gr/day) will be equal to or greater than the established value; while in milk production per lactation the maximum value is 2061.1 (kg/lactation) belonging to a female bovine with 14 liters per day, which has a milk weight of 14.42 (kg/lactation).